Association Between C-Reactive Protein–Triglyceride Glucose Index and Depressive Symptoms Among US Adults: A Nationally Representative Cross-Sectional Study From 2005 to 2023. - Liu, Dan; Qi, Wenye; Zhu, Chunying (Actas Espanolas de Psiquiatria, 2026)
Background/Objective: Depressive disorders represent a major global health challenge, with inflammation and insulin resistance identified as key pathophysiological factors. The C-reactive protein–triglyceride glucose index (CTI), a novel composite biomarker integrating the inflammatory and metabolic pathways, has demonstrated enhanced predictive value in cardiometabolic diseases. However, its relationship with depression remains unexplored. This study examined the association between CTI and depressive symptoms in a nationally representative U.S. adult population. Methods: We conducted a cross-sectional analysis using National Health and Nutrition Examination Survey data from 2005 to 2023. Depressive symptoms were assessed using the Patient Health Questionnaire-9, with scores ≥10 indicating clinically significant symptoms. CTI was calculated as 0.412 × Ln(CRP) + Ln[triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Multivariable logistic regression models were employed to evaluate CTI–depression associations, adjusting for sociodemographic factors, comorbidities and laboratory parameters. Restricted cubic spline analysis assessed dose–response relationships, and subgroup analyses examined consistency across demographic and clinical strata. Results: Among 15,318 participants (mean age 48.97 years; 49.78% female), 8.73% exhibited depressive symptoms. After comprehensive adjustment, each unit increase in CTI corresponded to a 23% increase in the risks of depression (odds ratio (OR) = 1.23, 95% confidence interval (CI): 1.11–1.36, p = 0.0001). Participants in the highest CTI tertile demonstrated 48% elevated odds compared with those in the lowest tertile (OR = 1.48, 95% CI: 1.17– 1.86, p = 0.0009), with a significant linear trend (p for trend = 0.0005). Restricted cubic spline analysis confirmed a linear dose–response relationship (p for nonlinearity = 0.1665). Associations remained consistent across age, sex, race/ethnicity and comorbidity subgroups (all p for interaction >0.05). Conclusion: Elevated CTI levels are independently associated with increased depression risk in U.S. adults, demonstrating a linear dose–response relationship. CTI may serve as a practical screening tool for identifying individuals at heightened depression risk, enabling integrated cardiometabolic–mental health interventions.